A PREDICTIVE METHOD FOR VERTICAL WELL PERFORMANCE IN BOTTOM WATER DRIVE RESERVOIR - SATIM (NIM : 22208318) , ADEK
Water zone underlaying an oil zone can provide energy for the oil reservoir to push more oil to the wellbore. While pushing the oil, the bottom water invades into the oil zone, resulting in the plane of water oil contact (WOC) to move upward. The upward movement will occur throughout the reservoir if the production rate does not exceed a certain critical rate. When production rate is a higher than the critical rate, water below the perforation interval will move fast toward the wellbore and the cone of water will develop. The first time the water reaches the wellbore is called as water breakthrough. Since then water cut tends to increase with producing time, causing a continuous decrease in oil production. Performance prediction of oil production for such systems with water coning is needed to evaluate the economics of the well. Simple and quick methods to predict the needed production preformance are rarely available in the literature. This study develops a predictive method for a vertical well performace in a bottom water drive reservoir. This method can estimate oil production by calculating water cut for a given withdrawal rate so that the oil production can be calculated. This is very helpful in early assessment of the well economics.